Ultrasound-Guided Serratus Plane Block and Fast-Track Tracheal Extubation in the Operating Room for Thoracic Trauma Patients: A Case Report. Issue 11 (1st December 2017) - Fusco, Pierfrancesco; Scimia, Paolo; Di Carlo, Stefano; Testa, Ambra; Luciani, Antonio; Petrucci, Emiliano; Marinangeli, Franco
Abstract : Painful rib fractures may be a factor in trauma patients remaining intubated and being given postoperative mechanical ventilation after emergency surgery. Regional techniques could provide sufficient analgesia in these patients to enable weaning and extubation and thus prevent or minimize complications related to prolonged ventilatory support. We describe a trauma patient with multiple rib fractures requiring an emergency splenectomy for whom an ultrasound-guided serratus plane block provided good quality pain relief for his rib fractures and enabled fast-track extubation in the operating room.